Effect of Zinc Source Fed at Nutritional Levels on Finishing Pig Growth Performance and Carcass Characteristics - Julian Arroyave; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Robert D. Goodband; Katelyn N. Gaffield; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 2,363 pigs (PIC 337 × 1050; initially 59.3 ± 1.35 lb) were used in a 122-d study to compare the effects of four different Zn sources on growth performance and carcass characteristics of finishing pigs raised under commercial conditions. Pigs were housed in mixed-sex pens with 26 or 27 pigs per pen and 22 pens per treatment. The four dietary treatments were arranged in a randomized complete block design and consisted of four Zn sources, all added at 100 mg of Zn/kg of diet. The Zn sources included ZnSO4, two sources of Zn hydroxychloride (source A = Hydroxy Zn, SAM Nutrition, Bloomington, MN; source B = Intellibond Z, Selko, Indianapolis, IN), and a chelated Zn source (B-Traxim 2C Zn-260, Pancosma, Rolle, Switzerland). The Zn source was added to diets in four separate vitamin-trace mineral premixes and was the only source of added Zn in the diet. Corn-soybean meal-DDGS (20% in phases 1 to 3 and none in phase 4) based diets fed in meal form were used in a four-phase feeding program. All diets were formulated to meet or exceed NRC (2012) requirement estimates within each phase. When the average weight of pigs in the barn was approximately 240 lb, the three heaviest pigs per pen were marketed, with remaining pigs marketed approximately 25 d later. On the last day of the experiment, pigs were weighed, tattooed on a pen basis, and sent to a commercial packing plant to determine carcass yield and characteristics. No differences (P > 0.10) between Zn sources were observed for growth performance, mortality, removals, total removals and mortality, HCW, carcass yield, and loin depth. A marginal Zn source response was observed for backfat depth (P = 0.095) and percentage lean (P = 0.072), mainly driven by pigs fed Zn hydroxychloride source B having numerically higher backfat and lower percentage lean compared to pigs fed all other Zn sources. However, no means separation was observed. In conclusion, the Zn sources used in this experiment did not significantly affect finishing pig growth performance or carcass characteristics, except for a marginal difference between Zn sources for backfat and percentage lean.
Keywords: carcass characteristics; growth performance; organic zinc; zinc hydroxychloride; zinc sulfate